Polymorphism of CLE gene sequences in potato - M. S. Gancheva; M. R. Losev; A. A. Gurina; L. O. Poliushkevich; I. E. Dodueva; L. A. Lutova (Вавиловский журнал генетики и селекции, 2021)
CLE (CLV3/ESR) is one of the most important groups of peptide phytohormones: its members regulate the development of various plant organs and tissues, as well as interaction with some parasites and symbionts and response to environmental factors. In this regard, the identification and study of the CLE genes encoding the peptides of this group in cultivated plants are of great practical interest. Relatively little is known about the functions of CLE peptides in potato, since the CLE genes of the potato Solanum phureja Juz. et Buk. were characterized only in 2021. At the same time, potato includes plenty of tuberous species of the genus Solanum L., both wild and cultivated, and the diversity of its forms may depend on differences in the sequences of CLE genes. In this work, we performed a search for and analysis of the CLE gene sequences in three wild potato species (S. bukasovii Juz., S. verrucosum Schltdl., S. commersonii Dunal) and four cultivated species (S. chaucha Juz. et Buk., S. curtilobum Juz. et Buk., S. juzepczukii Juz. et Buk., S. ajanhuiri Juz. et Buk.). In total, we identified 332 CLE genes in the analyzed potato species: from 40 to 43 genes of this family for each potato species. All potato species taken for analysis had homologues of previously identified S. phureja CLE genes; at the same time, the CLE42 gene, which is absent from the S. phureja genome, is present in all other analyzed potato species. Polymorphism of CLE proteins of S. commersonii is significantly higher than that of other analyzed potato species, due to the fact that S. commersonii grows in places outside the growing areas of other potato species and this potato is probably not one of the ancestors of cultivated potato. We also found examples of polymorphism of domains of CLE proteins that carried different functions. Further study of potato CLE proteins will reveal their role in development, including regulation of productivity in this important agricultural crop.